ANALISIS EFISIENSI BIAYA DAN WAKTU PADA PROYEK PEMBANGUNAN JALAN DUSUN BALIMBONGAN DESA TUNGKA KABUPATEN ENREKANG - Nur Ichsan; Ir. Saleh; Ir. Inarmiwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the cost and time efficiency of the Road Construction Project in Dusun Balimbongan, Tungka Village, Enrekang Regency, which was implemented through a community self-managed (swakelola) system. The study was motivated by the importance of cost and time control as key indicators of successful construction project implementation. The research employed a descriptive method with a quantitative approach. Data were collected through field observations, interviews, documentation, and analysis of project documents, including the Budget Plan (Rencana Anggaran Biaya/RAB), actual project costs, and project implementation schedule. Interviews were conducted with four key informants consisting of the Village Secretary, the Head of the Project Implementation Team (TPK), the Village Treasurer, and the Chief Foreman. Data were analyzed using cost efficiency analysis, time efficiency analysis, deviation analysis, and identification of factors influencing project implementation. The results showed that the planned project cost was IDR 60,000,000, while the actual project cost was IDR 59,575,000, resulting in a cost efficiency value of 0.71%, indicating a cost saving of IDR 425,000. Furthermore, the planned project duration was 11 effective working days, while the actual completion time was 9 effective working days, resulting in a time efficiency value of 18.18%, indicating that the project was completed two days earlier than scheduled. Factors influencing project implementation included weather conditions, labor productivity, material availability, supervision through the community self-managed system, and decision-making through community deliberation. Based on the findings, the project achieved cost savings and was completed earlier than planned. However, this study is limited to cost and time aspects and does not include technical quality testing of the completed construction work.Keywords: Cost Efficiency, Time Efficiency, Deviation Analysis, Village Self-Managed Project (Swakelola), Road Construction Project.